Parents of poor children in England 1580 - 1800 - Crawford, Patricia 1941-2009 (Oxford Univ. Press, 2010)
A study of the mothers and fathers of poor children in early modern England, drawing upon a wide range of archival material, including quarter session records, petitions for assistance, applications for places in the London Foundling Hospital, and evidence from criminal trials in London's Old Bailey.